Non-Test Portfolio Assessment Techniques: Innovation to Improve Maharah Al-Kitabah - Muhammad Khotibul Umam; Adik Laila Fitri Nawangsari; Isyqie Firdausah (Lembaga Sosial Rumah Indonesia, 2023)
Portfolio assessment is an ongoing evaluation based on collecting assignments and information from students to show the progress of competency development over a certain period. The method used in this research is action research, where researchers can be directly involved in improving the quality of lectures, which is reflected in improving students' writing skills. Then the researcher engages in reflection on the problem, collects and analyzes data, and implements changes or an action plan based on the reflection results. The purpose of this study Islam to improve the Arabic writing skills of library science students at UIN Sunan Kalijaga Yogyakarta by using portfolio assessment. The research results show that portfolio assessment innovations can improve the writing skills of Library Science students at UIN Sunan Kalijaga Yogyakarta.